Conjoint Analysis to Measure Millennial Generation's Preferences on the Role of Technology in the Existence of Mitra Batik Cooperatives in Tasikmalaya - Sastika, Widya; Hanifa, Fanni Husnul; Kusumahadi, Krishna; Marcelino, Dandy (Jurnal Penyuluhan, 2024)
As a people's economic movement founded on the concept of kinship, a cooperative is a corporate company made up of individuals or cooperative legal entities that engage in cooperatively-based activities. In the city of Tasikmalaya alone there are 603 ooperatives with an active level of 44%. Mitra batik cooperative is one of the oldest consumer cooperatives in Tasikmalaya. In an effort to develop cooperatives, mitra batik cooperatives are faced with a situation where they still have various obstacles for their development, one of which is the low interest and awareness of the community members to participate in cooperatives. In an effort to increase the number of cooperative members, the authors intend to conduct research on the preferences of Tasikmalaya people, especially millennial generation to participate in maintaining the existence of mitra batik cooperatives. The method used is conjoint analysis. According to the research results, millennials consider technology the most significant aspect in preserving mitra batik cooperatives in Tasikmalaya. In the digital age, technology is a crucial element. Millennials like technology's ease. The millennial generation must develop technology to preserve mitra batik cooperatives in Tasikmalaya. Due to the fast expansion of banking, particularly in technology, cooperatives must keep up with technology.